Infinite Existence Solutions of Fractional Systems with Lipschitz Nonlinearity. (17th December 2020) - Guefaifia, Rafik; Boulaaras, Salah Mahmoud; Cherif, Bahri; Radwan, Taha
Abstract : The paper deals with the existence of infinitely many solutions of a class of perturbed nonlinear fractional p -Laplacian differential systems using one control parameter combined with the variational method.